Editorial - Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2020)
“Commission Staff Working Document. Annex II. Results of the public consul- tation on the EU’s modernisation agenda for higher education” presents “the key findings of the public consultation on the future of the EU’s agenda for the mod- ernisation of higher education systems. The results of the consultation underpin the specific initiatives related to higher education presented in the Skills Agenda and will inform the EU’s future strategy for the modernisation of higher educa- tion. […] A second area where skills gaps are highlighted in the consultation responses encompasses the broad fields of Science Technology, Engineering and Maths (STEM), where many national authorities and stakeholders see a need to strengthen high-level skills provision. In particular, several contributions note a specific need for more ICT specialists and for students across the board to acquire better digital skills” (http://ec.europa.eu/social/main.jsp?catId=1223&langId=en &moreDocuments=yes, accessed 15 November 2016). The present volume includes nine papers gathered in four chapters. Chapter I “High-tech Electronic Learning Environment Design”; Chapter II, “ICT Literacy Development”, Chapter III – “Methodological Aspects of E-learning”, the last chapter, entitled “Reports”. The papers presented in this volume show results of different studies conducted by researchers from different countries. The findings are certainly useful for fur- ther successful implementation of the strategy to develop a smart, sustainable, and inclusive society of the 21st century.